2008
DOI: 10.1002/chir.20539
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic crystal growth, differential circular scattering, and the origin of biomolecular homochirality

Abstract: Phthalic acid rapidly crystallizing in thin aqueous films is deposited radially and rhythmically as dendritic banded spherulites that have heterochiral meso-textures in hemi-circles. The chiral fields differentially scatter left and right circularly polarized light. A scenario for chiral amplification and the origin of biomolecular homochirality is thus proposed that combines the influences of crystals and light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 85 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…This led to numerous suggestions and a quest for finding the appropriate amplification mechanism for symmetry-breaking scenarios at various stages of the emergence of life [241][242][243][244][245]. Among the various symmetry-breaking scenarios, chemical reactions at crystal surfaces or asymmetric crystallization processes have been considered [246][247][248]. If surface mirror-symmetry breaking effects, like those discussed in Section 5, can be combined with larger symmetry-breaking effects, like the Soai reaction [249] or even self-replicating systems chemistry, the reward for enantioselective synthesis as well as insight into the complex symmetry-breaking scenarios of homochirality will be tremendous.…”
Section: Diastereomers and Diastereomeric Recognitionmentioning
confidence: 99%
“…This led to numerous suggestions and a quest for finding the appropriate amplification mechanism for symmetry-breaking scenarios at various stages of the emergence of life [241][242][243][244][245]. Among the various symmetry-breaking scenarios, chemical reactions at crystal surfaces or asymmetric crystallization processes have been considered [246][247][248]. If surface mirror-symmetry breaking effects, like those discussed in Section 5, can be combined with larger symmetry-breaking effects, like the Soai reaction [249] or even self-replicating systems chemistry, the reward for enantioselective synthesis as well as insight into the complex symmetry-breaking scenarios of homochirality will be tremendous.…”
Section: Diastereomers and Diastereomeric Recognitionmentioning
confidence: 99%
“…In another recent study it was shown, by circular dichroism, that achiral phthalic acid crystallizes as thin films that are deposited radially and rhythmically as dendritic banded spherulites that have heterochiral meso-textures in semicircles. , …”
Section: Enantiomorphous 3d Crystals For “Mirror-symmetry Breaking”mentioning
confidence: 99%
“…The circular birefringence, usually presented phenomenologically as circular retardance (CR), measured in these instances does not arise from natural optical activity, a consequence of the dissymmetry of polarizable groups within a molecule (78) or a single crystal (79). Rather, it stems from the dissymmetry of anisotropic crystallites with respect to one another (Figure 5) (80)(81)(82)(83)(84)(85)(86)(87).…”
Section: Mesoscale Polarimetrymentioning
confidence: 99%